‘Unwasting’ waste: Valorisation of cocoa pod husks for black soap production - Rülke, Jana; Arnold, Hannah; Franz, Martin (ERDKUNDE, 2025)
This article examines how agricultural waste - in the form of cocoa pod husks (CPHs) - can be valorised through integration into alternative production networks. Drawing on the case of CPH-based black soap production in Ghana, we use the Global Production Network (GPN) approach to analyse how local value creation and enhancement of agricultural waste is affected by underlying production network structures. We argue that the transformation of CPHs into soap represents both a spatial and structural shift: although CPHs originate within the global cocoa-chocolate production network, their revaluation unfolds in a distinct, small-scale, locally embedded production network. This overlap creates frictions that constrain value capture, particularly for small-scale producers. Based on qualitative interviews, we show how actors’ embeddedness - societal, territorial, and network embeddedness - mediates upgrading opportunities. While cosmetic companies benefit from greater network embeddedness and capital, small-scale producers face regulatory barriers, information asymmetries, and limited collective organisation. Although cocoa farmer cooperatives represent important agents of collective power, existing support schemes often fail to align these structures with the specific requirements and dynamics of black soap production networks. By integrating literature on agricultural by-products, waste, and upgrading into GPN analysis, the article contributes to a deeper understanding of value creation beyond conventional production networks and calls for more inclusive and network-sensitive development strategies.